Epigenetic silencing of clustered tRNA genes in Arabidopsis. Issue 18 (17th September 2020) - Hummel, Guillaume; Berr, Alexandre; Graindorge, Stéfanie; Cognat, Valérie; Ubrig, Elodie; Pflieger, David; Molinier, Jean; Drouard, Laurence
Abstract: Beyond their key role in translation, cytosolic transfer RNAs (tRNAs) are involved in a wide range of other biological processes. Nuclear tRNA genes (tDNAs) are transcribed by the RNA polymerase III (RNAP III) and cis -elements, trans -factors as well as genomic features are known to influence their expression. In Arabidopsis, besides a predominant population of dispersed tDNAs spread along the 5 chromosomes, some clustered tDNAs have been identified. Here, we demonstrate that these tDNA clusters are transcriptionally silent and that pathways involved in the maintenance of DNA methylation play a predominant role in their repression. Moreover, we show that clustered tDNAs exhibit repressive chromatin features whilst their dispersed counterparts contain permissive euchromatic marks. This work demonstrates that both genomic and epigenomic contexts are key players in the regulation of tDNAs transcription. The conservation of most of these regulatory processes suggests that this pioneering work in Arabidopsis can provide new insights into the regulation of RNA Pol III transcription in other organisms, including vertebrates.